School climate: the controllable and the uncontrollable. Issue 3 (27th May 2018) - Sulak, Tracey N.
Abstract: A positive school climate impacts students by promoting positive relations among students, staff and faculty of the school. The current study used latent class analysis and multinomial regression with R3STEP to analyse patterns of negative behaviours in schools and test the association of these patterns with structural variables like school size, demographics, and location using data from the 2008 School Survey on Crime and Safety, ( n = 2560). The results indicated five classes of frequencies of negative behaviours. By using the lowest frequency of behaviour class as a reference, the classes with the highest frequencies of bullying, teacher disrespect, and sexual assault were more likely to be found in high crime areas and have larger campuses serving over 1000 students. Implications include the need to serve subgroups of schools based on measurable variables and the need to educate future teachers, administrators, and school psychologists about school climate and positive behaviour support systems.